Aktivitas Antibakteri Kombinasi Ekstrak Daun Mengkudu (Morinda citrifoli L.) dan Bawang Putih (Allium sativum) terhadap Escherichia coli dan Staphylococcus aureus: Antibacterial Activity of Noni Leaf Extract (Morinda citrifoli L.) and Garlic (Allium sativum) against Escherichia coli and Staphylococcus aureus - Lestari, Indah; Hanum, Galuh Ratmana (Medicra (Journal of Medical Laboratory Science/Technology), 2019)
Indonesia is a nation with rich medicinal plants. Medicinal plants can be used for the treatment of diseases due to bacterial infection. Noni leaf (Morinda citrifolia) and garlic (Allium sativum) are medicinal plants and herbs that have the potential to inhibit or kill Escherichia coli and Staphylococcus aureus. The aim of this research is to know the antibacterial activity on the combination of extract noni leaf (Morinda citrifolia) and garlic (Allium sativum) to growth of Escherichia coli and Staphylococcus aureus. In this study using a research design that is a complete randomized design with purposive judgment sampling method.Anti-bacterial activity test performed by the disk diffusion method. The concentration of extract used is 10%, 30%, 60% and 90%. The analysis was done by Kruskal-Wallis test. The results of this study showed that a combination of 30% leaf extract and 10% garlic extract able to inhibit the growth of Staphylococcus aureus bacteria optimally with the average area of the inhibit zone is 12 mm. While on the combination of 30% noni leaf extract and 90% garlic extract able to inhibit the growth of Eschericia coli optimally with the average area of inhibit zone is 22,27 mm.